Penyuluhan Peningkatan Gizi Ibu Hamil Melalui Konsumsi Protein Hewani Dan Nabati - Irma Erpiani; Juenita Elfunam Mado; Nur Rahma Srifitayani; Nurul Annisa; Rischa Hamdanesti (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Adequate nutrition during pregnancy is a crucial factor in supporting maternal health and fetal growth and development. Insufficient protein intake, both animal and plant-based, can increase the risk of anemia, chronic energy deficiency (CED), low birth weight, and other pregnancy complications. However, many pregnant women still do not understand the importance of consuming a balanced and diverse protein diet. This Community Service activity aims to increase the knowledge and awareness of pregnant women regarding the importance of consuming animal and plant-based protein as an effort to improve nutritional status during pregnancy. Implementation methods included nutrition counseling, interactive discussions, food selection simulations, and evaluation through pre- and post-tests. The results of the activity showed a significant increase in pregnant women's knowledge about protein sources, the benefits of protein for pregnancy, and recommended protein consumption patterns. This activity is expected to encourage changes in pregnant women's eating behavior towards a balanced nutritional diet.